Offshore back office operations : supplying support services to global markets (ITC GenevaCH, 2000)
Focuses on back office operations (distance delivery of range of non-core service functions), as a way of doing business that offers significant business opportunities for governments and service firms in developing and transitional economies. Explains phenomenon and types of back office operations also how to determine back office operations as a deliberate development strategy. Delineates structure for a back office promotional initiative and addresses competitiveness issues. Outlines how tro attract foreign investors or clients for local suppliers. Gives examples of strategies that various countries have used to develop back office capabilities.
Keywords: SERVICE INDUSTRY